Facile Preparation of 2D Nitrogen and Sulfur Co-Doped Porous Carbon Nanosheets for High-Performance Supercapacitors. Issue 12 (9th July 2019) - Wang, Guiqiang; Liu, Jieqiong; Dong, Weinan; Yan, Chao
Abstract : 2D nitrogen and sulfur co-doped porous carbon nanosheets (NSPCSs) are facilely prepared from methyl orange (MO) doped 1D polypyrrole (PPy) nanotubes by an one-step heat-treating process in the presence of KOH under nitrogen atmosphere. The combination of the dedoping owing to the interreaction between MO and KOH, the pyrolysis of PPy, and the activation by KOH at high temperature results in the damage and exfoliation of PPy nanotube, and finally forms 2D NSPCSs. As-prepared NSPCSs possess high surface area, large pore volume, and hierarchical porosity. This unique architecture constructs interconnected electrolyte-transport channels, shortens the ion-diffusion path, and provides large accessible surface area. In addition, co-doping of nitrogen and sulfur not only enhances the wettability of carbon materials but also provides pseudocapacitance. As a result, the specific capacitance of NSPCNSs can reach up to 300.8 F g −1 . Furthermore, NSPCSs display good rate capability (192.9 F g −1  remained at 20 A g −1 ) and excellent cycling stability (97.5% retention over 10000 cycles). The assembled two-electrode device delivers an energy density of 8.19 Wh kg −1 at a power density of 0.3 kW kg −1 .